VR4VRT: Virtual reality for virtual Rowing training - van Delden, R.; Bergsma, S.; Vogel, K.; Postma, D.; Klaassen, R.; Reidsma, D. (CHI PLAY '20: Extended Abstracts of the 2020 Annual Symposium on Computer-Human Interaction in Play. November 2020, 2020)
Learning how to properly row is an intensive and injury prone process. Ergometers (i.e., rowing machines) are used as a preparatory step to train the basic steps of rowing, as well as to further improve technique and maintain stamina. In this paper we present three design iterations resulting in a new interactive system that utilizes the commercially available dynamic ergometer (RP3). Our proposed software-hardware combination uses the RP3 with the HTC Vive platform extended with three location trackers, from which the software is available on request. We will showcase how this facilitates a range of opportunities.